THE EFFECT OF REWARDS AND PUNISHMENT ON EMPLOYEE PERFORMANCE ACHIEVEMENT INPT. NURLENNI KAHAR SPBU 7492212 NORTH GALESONG AXLE - Nur Selviati; Muhammad Rusdi; Samsul Rizal (CV. AFDIFAL MAJU BERKAH, 2024)
The purpose of this research is to determine the effect of rewards on employee performance and punishment on employee performance at PT. Nurleni Kahar SPBU 7492212 North Galesong Axle. The sample used in this research was 33 respondents using the census method or saturated sample. The type of research data used in this research is quantitative data. Data collection was carried out by observation and questionnaires distributed to respondents. In this research, the data collected includes primary and secondary data. The analysis method used is multiple klinear regression using the SPSS program. The research results show that rewards have a positive and significant effect on employee performance and punishment has a positive and significant effect on employee performance at PT. Nurleni Kahar SPBU 7492212 North Galesong Axle